Public Expenditure and Financial Accountability Assessment : Federal Democratic Republic of Ethiopia (Oromia National Regional State) - World Bank (World Bank, Washington, DC, 2020)
The objective of the Public Expenditure and Financial Accountability (PEFA) assessment is to review the current performance of the public financial management (PFM) systems, processes, and institutions of the Oromia regional government since the last assessment in 2015. The assessment is aimed at assisting the government in identifying PFM weaknesses that may inhibit effective delivery of services to its citizens and the realization of its development objectives in general. Furthermore, the findings of the PEFA assessment will assist the government to develop a PFM reform strategy and provide the basis for a coherent PFM reform program that can be supported by development partners as well as through the government’s own initiatives. The Oromia assessment covered regional government budgeted units, extra-budgetary units, the Office of Regional Auditor General (ORAG), the regional council, and public enterprises. The assessment shows the state of PFM performance of the region at the time of the fieldwork in November 2019.